Never-ending caring : the experiences of caring for a child with cerebral palsy : a thesis presented in fulfillment of the requirements for the degree of Doctor of Philosophy in Nursing at Massey University, Palmerston North, New Zealand - Klankaradi, Kuephan (Massey University, 2008)
Cerebral palsy is one of the chronic conditions which have become a serious health burden worldwide. Consequently, this health burden involves healthcare as a whole, regardless of whether the focus is on the macro or micro system. Glaserian grounded theory was employed to explore and explain the experiences of families who have a child with cerebral palsy, particularly in the Thai cultural context. Unstructured interviews and participant observations were used along the process of data collection from 15 families who have a child with cerebral palsy. Data encompassed a variety of qualitative data sources: interviews, observational field notes, personal documents, pictures, drawings, and information from a literature review. The process of data analysis was guided by Glaserian grounded theory throughout the processes of constant comparative analysis to generate a substantive theory. The substantive theory comprised three core categories: Enduring despair, culture of obligation and responsibility and living with, which were integrated into the basic social psychological process of never-ending caring. The metaphor of a waterwheel was used to depict the basic process. The substantive theory of never-ending caring for a child with cerebral palsy provided an explicit understanding of the experiences of these families in day-to-day living with, and care of, a child with cerebral palsy. It is hoped that this understanding will be a constituent of health care - particularly of people with chronic conditions, whereby the practice of healthcare professionals will improve, thus enhancing the efforts of their work to achieve the ultimate goal of improving the quality of life of children with cerebral palsy and their families.
Keywords: Children with cerebral palsy; Families of cerebral palsied children; Thailand; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321209 Family care